Gold nanoparticle delivery-enhanced proteasome inhibitor effect in adenocarcinoma cells. (October 2013) - Coelho, Sílvia Castro; Rocha, Sandra; Juzenas, Petras; Sampaio, Paula; Almeida, Gabriela M; Silva, Filipe Santos; Pereira, Maria Carmo; Coelho, Manuel A N
<x xml:space="preserve">Abstract</x> Background: Proteasome inhibition is a current therapeutic strategy used in the treatment of multiple myeloma. Drugs controlling proteasome activity are ideally suited for unidirectional manipulation of cellular pathways such as apoptosis. The first proteasome inhibitor approved in clinics was bortezomib. This drug is currently used in combination with other anticancer agents. Objectives : In this study, the enhancement of bortezomib activity was evaluated using gold nanoparticles coated with poly(ethylene glycol). The uptake mechanism of the gold nanoparticles in pancreatic cell lines, S2-013 and hTERT-HPNE, was assessed by laser scanning confocal microscopy (LSCM). Results: Pancreatic cancer cells internalized the nanoparticles together with the drug in few minutes through the formation of endocytic vesicles. This rapid uptake leads to an increase in the concentration and diffusion of bortezomib in the cytoplasm yielding an increased toxicity on the cells when compared to the drug alone. Conclusion: Gold nanoparticles can be used as effective delivery systems to increasing the permeation and retention of drugs in cancer cells.